Children's lives and schooling across societies - Hannum, Emily; Fuller, Bruce (Amsterdam ; Oxford : Elsevier JAI, 2006)
In recent decades, sociological research has investigated the nature of the school institution and its uneven effects on the progress of families, societies, and the global community. Yet, relatively little comparative research on schooling has dealt in a serious way with links between schooling and the other major contexts of childhood: families and communities. This edition of "Research in the Sociology of Education" speaks to the diverse contexts in which children function around the world, and to how these contexts shape school experiences and outcomes. The edition's authors are international and interdisciplinary. They offer a pastiche of perspectives on a single topic: how the non-school contexts of childhood interact with the school institution to advance modern and not-so-modern forms of virtue, merit, and attainment, in cultural context. This book offers qualitative and statistical portraits of children living in Asian and African countries. It links educational opportunities to the child's socialization. It urges social scientists and policy makers to consider a child's surroundings when modeling the modern school system. This book series is available electronically online.
Overview: children's lives and schooling across societies / Emily Hannum and Bruce Fuller -- Community matters in China / Jennifer H. Adams -- Social capital formation through Chinese school communities / Heidi Ross and Jing Lin -- Girls' schooling and marriage in rural Bangladesh / Simeen Mahmud and Sajeda Amin -- Gendered homes and classrooms in rural Nepal / Jennifer Rothchild -- Families, schools, and reading in Asia and Latin America / Hyunjoon Park and Gary D. Sandefur -- The contexts of children's lives in Asia: families, schools and communities : Commentary on Adams, Ross and Lin, Mahmud and Amin, Rothchild, and Park and Sandefur / Emily Hannum -- Children's work and school attendance in Ghana / Niels-Hugo Blunch -- Demand for schooling among orphans in Zimbabwe / Craig Gundersen, Thomas Kelly and Kyle Jemison -- Children's work, health, and school demand: commentary on Blunch and Gundersen et al. papers / Bruce Fuller -- Alienation from learning - poor Ethiopian children in Israel / Gad Yair and Orit Gazit -- Home environs and alienation from schooling: commentary on Yair and Gazit / Daniel Bekele.
Description based on print version record.
Keywords: Educational sociology; Education; Age groups: children; Education -- General; Social Science -- General; Electronic books